SOLUSI SUMBER PEMBIAYAAN JALAN DI ERA OTONOMI DAERAH - Nuriyanis, Akhmad (UMP, 2010)
The Indonesian nation began to promote the reform era of regional autonomy, contribute significantly to the local independence, on the other hand the level of investment in road infrastructure in Indonesia in general tend to be less adequate. These conditions have an impact on decreasing the level of system efficiency and effectiveness of planning, implementation and maintenance of existing infrastructure, with consequent emergence of an urgent need to establish the accuracy of the policy directions that can ensure the availability of financing road maintenance is continuous.Concept of in developed countries by way of charge on road users directly as a function of fixed costs and variable costs of road class, management and maintenance, and can provide enough income for the implementation of the road program, by providing an institutional device whereby certain income streams can be channeled to public sector units which can be used without going through the procedures and review of the general budget. Source of income consists of the fuel tax, vehicle tax, vehicle weight, fines for overloading. As an illustration of current conditions, road maintenance costs resulting from fuel tax revenues to cover ± only 25% of the total maintenance funding requirements, while in another country fuel tax revenues reached ± 90%. Key Words: Financing Road, Autonomy, Road Revenue,.